Perilaku Remaja tentang Penerapan Pencegahan Covid-19 - Yusfia Ari Azizah (Institut Teknologi, Sains, dan Kesehatan RS dr. Soepraoen Malang, 2021)
Introduction The lack of application of behavior to health protocols carried out by teenage visitors at Bangbros Cafe Rampal Malang City has an impact on increasing the spread and accelerating the transmission of Covid-19 from Cluster Cafe. The purpose of the study was to determine the level of adolescent behavior regarding the implementation of Covid-19 prevention at Bangbros Cafe Rampal, Malang City. Methode The research design used a quantitative descriptive design. The population is all 118 teenagers using purposive sampling based on inclusion criteria with a sample of 73 teenagers at Bangbros Caffe Rampal Malang City on January 19-26 2021. The research variable is adolescent behavior regarding the implementation of Covid-19 prevention. The research instrument used a questionnaire, the data that had been obtained were analyzed by percentage univariate analysis. Results From the results of the study, a small proportion of teenagers behaved well, 14 teenagers (19%), almost half of them behaved fairly 32 teenagers (44%) and almost half of teenagers behaved less 27 teenagers (37%). Conclusion From the results of the study, it is hoped that adolescents will increase their motivation to actively seek information on preventing Covid-19 in adolescents and be more supportive of government program activities in increasing adherence to Covid-19 prevention protocols in adolescents. Keywords: Adolescent Behavior, Implementation of Covid-19 Prevention